Quantification of plasma microRNAs in a group of healthy smokers, ex-smokers and non-smokers and correlation to biomarkers of tobacco exposure. (March 2015) - Banerjee, Anisha; Waters, David; Camacho, Oscar M.; Minet, Emmanuel
Abstract The stability of circulating miRNAs, their non-invasive sampling techniques and deregulation in diseases make them potential candidate biomarkers of biological effect. Here, we profiled the level of 84 plasma miRNAs in 30 smokers, 20 non-smokers and 20 ex-smokers. A robust statistical strategy was applied with replicate samples to account for reproducibility of the results. We identified differential expression of miR-124 and let-7a between the smoking and control groups. We further explored the dose–response relationship of miR-124 and let-7a with two biomarkers of tobacco exposure and found that this relationship was affected by adjustments based on age, pack-year and gender.